Maternal Concerns in Home Care for the Premature Newborn: An Integrative Review - Thaís Emanuele da Conceição; Maria Helena do Nascimento Souza; Rafael Braga Esteves; Patrícia Lima Pereira Peres; Donatella Valente; Antonella Nespoli (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To identify and analyze the scientific literature, both national and international, concerning the primary maternal concerns about caring for premature newborns at home. Methods: This integrative review is based on the guiding question: "What scientific publications from 2012 to 2021 address maternal concerns about the care of premature newborns at home?". Searches were conducted in the electronic databases: Embase, Medline, Web of Science, Lilacs, Scielo, and Cochrane Library. Results: A total of 21 articles were identified. The qualitative analysis showed that maternal concerns pertained to breastfeeding, hygiene, sunbathing practices, managing infant colic, identifying signs, symptoms, and clinical changes, temperature control, and the third phase of the kangaroo method. Conclusions: Maternal uncertainties underscore the importance of enhancing strategies focused on supporting families and ensuring continued care for neonates at home.